Child temperament as a longitudinal predictor of mother-adolescent interaction quality: are effects independent of child and maternal mental health? - Fleck, Leonie; Fuchs, Anna; Williams, Katharina; Möhler, Eva; Resch, Franz; Koenig, Julian; Kaess, Michael (European child & adolescent psychiatry, 2024)
Adaptive parent-child interaction plays a major role in healthy child development. Caregiver mental health problems can negatively impact parent-child interaction. In turn, interactional quality is often studied as a predictor of child outcome. However, child characteristics supposedly shape parent-child interactions as well. Given associations between child and caregiver mental health and child temperament, this study aimed at differentiating their effects on dyadic interaction quality in adolescence. Child temperament and character at age 5 were investigated as longitudinal predictors of observed mother-adolescent interactional quality at age 14 in a community sample (N = 76). It was examined whether these effects were independent of maternal and child mental health and earlier dysfunctional interaction. Lower novelty seeking, higher reward dependence, and higher cooperativeness separately predicted higher dyadic interactional quality at age 14. Controlling regressions for dysfunctional interaction at age 5, which was a significant negative predictor of later interactional quality, cancelled out the effects of novelty seeking and cooperativeness. Past or concurrent maternal or child psychopathology did not explain variance in mother-adolescent interaction. Applying backward selection, a model including reward dependence and dysfunctional interaction at age 5 and concurrent maternal stress showed the best fit for explaining dyadic interaction quality. Results suggest that enduring rather than transient child features predict interactional quality in a community sample. Effects of temperament are not better explained by those of psychopathology, but a combination of child, maternal, and dyadic features predicted dyadic behaviour best. Selective prevention should target parenting in the context of challenging child characteristics specifically.
Gesehen am 13.03.2024